Development Of Problem-Based Learning Geography Teaching Modules To Improve Critical Thinking Skills In Biodiversity Materials Class XI - Rohmila Mayang; Sunarty Suly Eraku; Yayu Indrianti Arifin (International journal of technology and education research, 2025)
This study developed a Problem-Based Learning (PBL)–based Geography teaching module on Biodiversity for Grade XI students at SMA Negeri 2 Wonosari. The module was created to provide learning materials that encourage active participation and strengthen students’ critical thinking and problem-solving skills in addressing environmental issues. The research employed a Research and Development (R&D) approach using the 4-D model, consisting of Define, Design, Develop, and Disseminate stages. Validation results from module and material experts indicate that the teaching module is highly feasible for use, with a validity score of 87% from the module expert and 90% from the material expert, both falling into the “very good” category with minor revisions. Limited trials conducted with students produced scores ranging from 70% to 87%, placing the module in the “good” to “very good” category. The results also show that the PBL-based Geography module is effective in improving students’ critical thinking skills, with an average N-gain of 0.47 categorized as moderate. Significant improvement was observed particularly in students’ ability to provide simple explanations and draw conclusions related to biodiversity and its connection to environmental sustainability. Thus, the PBL-based Geography teaching module can make a positive contribution and serve as an alternative learning resource that supports the implementation of the Kurikulum Merdeka, particularly in enhancing quality learning and strengthening the Pancasila Student Profile through contextual and participatory learning